Dr. Ong’s Lens on Sarawak under the Japanese shadow. - Indraneil, Das (Philatelic Society of Kuching Sarawak, 2023)
The four years of Japanese rule of Sarawak was described in an article by Ong Liap Teck in an article in the Sarawak Museum journal. This review draws attention to a poorly understood period of the State's history, as recovered from a careful study of previously unavailable documentary sources.